Ear Leaf Photosynthesis and Related Parameters of Transgenic and Non-GMO Maize Hybrids - H. Arnold Bruns (International Journal of Agronomy)
Hybrid maize (Zea mays L.) through transgenics now includes δ-endotoxins for insect control and tolerance to the herbicides glyphosate and glufosinate. Some hybrids have multiple transgenic traits as part of their genotype (stacked gene). Limited information is available on how these traits alone affect A (net assimilation rate; µmol CO2 m−2 s−1) and related physiological parameters. A two-year, two-location, irrigated experiment comparing four stacked gene, four glyphosate tolerant, and two non-GMO hybrids for ear leaf A, gs (stomatal conductance; mol H2O m−2 s−1), Em (transpiration; mol H2O m−2 s−1), IWUE (intrinsic water use efficiency; (A/(gs*100))), and Ci (intercellular [CO2] µmol CO2 mol air−1) was completed at Stoneville, MS, in 2012. Data were collected at growth stages R1 (anthesis) and R2 (early kernel filling) using a Li-Cor LI-6400XT set at 355 μmol mol−1 CO2 with a flow rate of 500 μmol s−1 and a 6400-02 light source set at 87.5% full sunlight. Measurements were made between 08:30 h and 11:30 h CST, within 48 h of 25 ha mm irrigation and ≥33.0% cloud cover. Transgenic traits did not influence the physiological parameters of A, gs, Em, IWUE, or Ci during the critical growth stages of R1 or R2.